Smart-Kids: Rancangan Sistem Pembelajaran Berbasis Kecerdasan Buatan (AI) untuk Siswa Sekolah Dasar yang Menyenangkan, Adaptif, dan Berdaya - Taufiqurrohman Sayyaf; Nabila Zuama Muthoharoh; Yuli Puji Lestari (Jurnal Pendidikan dan Humaniora Rumbio, 2025)
This study designs and studies the SMART-Kids (Smart Modular Adaptive Responsive Teaching for Kids) system, an artificial intelligence (AI)-based learning system that aims to create a personal, adaptive, and enjoyable learning experience. The study was conducted at SDN Bayan No. 216 and SDN 2 Gemolong. Data collection techniques used interviews, observations and documentation with qualitative and quantitative data analysis techniques. This system is designed to analyze student learning patterns, adjust content according to interests and abilities, and provide real-time feedback to teachers and students. This study identifies essential needs, designs prototypes, and analyzes the potential impact of implementation. With this approach, it is hoped that a more inclusive learning process will be created and have a positive impact on the motivation and learning outcomes of elementary school students.